The U.S. – Japan Alliance and Asia-Pacific Security: implications for Japan-Taiwan relations - Kuo, Wen Kuo; Hsiang, Yi Yeh (Penerbit UKM, 2015)
The end of the Cold War has brought tremendous changes in the international system. In Asia, the most significant change has been the rise of China. Faced with China’s rapid economic growth and increased military threat, the United States has shifted its strategic focus to the Asia-Pacific region, strengthening defense cooperation with Japan. The Treaty of Mutual Cooperation and Security between the United States and Japan was initially a Cold War alliance to combat the threat of the Soviet Union. Due to its strategic position, Taiwan is a crucial part of the Western Pacific for the United States. For Japan, Taiwan is “Japan’s lifeline,” and is a major unspoken factor in Japan’s security policy considerations. Does security and stability in the Taiwan Strait influence trade and development and overall military balance in the wider Asia-Pacific region? This study looks at changes in security in the Taiwan Strait and Taiwan-Japan relations through the evolution of the U.S. – Japan Security Treaty.